Σχεδιασμός αφισών για την προαγωγή της γραφιστικής και τυπογραφικής επιμέλειας στην Κύπρο - Σλίτσανε, Ίνεσε (My University, 2024)
The purpose of this project is to design an awareness campaign with reference to the printing police and posters concerning some of the main printing crimes through the principles and values of printing. The study provides various research on the principles and values of typography as well as the typographic crimes that exist, also on colours, fonts and everything else that is involved in the use of typography. At the same time, there will be research and analysis on the typographic crimes on signs of shops and restaurants that are considered the main focus in Cyprus with misuse of typography.This will be followed by the design and implementation of the posters and logo of the typographic police. Then the selected audience will have the opportunity to evaluate the project and judge based on their own opinion. In conclusion, the posters include several typographic crimes that express the reasons about correct use of typography in short explanatory text.
Keywords: Typographical errors; Typography; Campaign; Signs; Τυπογραφικά σφάλματα; Τυπογραφία; Καμπάνια; Πινακίδες